Robust digital speech watermarking for online speaker recognition - Nematollahi, Mohammad Ali; Rosales, Hamurabi Gamboa; Akhaee, Mohammad Ali; Syed Mohamed, Syed Abdul Rahman Al-Haddad (Hindawi Publishing Corporation, 2015)
A robust and blind digital speech watermarking technique has been proposed for online speaker recognition systems based on Discrete Wavelet Packet Transform (DWPT) and multiplication to embed the watermark in the amplitudes of the wavelet's subbands. In order to minimize the degradation effect of the watermark, these subbands are selected where less speaker-specific information was available (500 Hz-3500 Hz and 6000 Hz-7000 Hz). Experimental results on Texas Instruments Massachusetts Institute of Technology (TIMIT), Massachusetts Institute of Technology (MIT), and Mobile Biometry (MOBIO) show that the degradation for speaker verification and identification is 1.16% and 2.52%, respectively. Furthermore, the proposed watermark technique can provide enough robustness against different signal processing attacks.